Surge my journey with General David Petraeus and the remaking of the Iraq War - Mansoor, Peter R. (Yale library of military history, 2013)
Using newly declassified documents, interviews, and published sources, a member of General David Petraeus' personal staff provides an insider account of the troop surge in Iraq and how key political leaders orchestrated it